2017
DOI: 10.1038/srep43298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of photocatalytic TiO2 powder under varied environments using near ambient pressure X-ray photoelectron spectroscopy

Abstract: Consecutive eight study phases under the successive presence and absence of UV irradiation, water vapor, and oxygen were conducted to characterize surface changes in the photocatalytic TiO2 powder using near-ambient-pressure X-ray photoelectron spectroscopy (XPS). Both Ti 2p and O 1s spectra show hysteresis through the experimental course. Under all the study environments, the bridging hydroxyl (OHbr) and terminal hydroxyl (OHt) are identified at 1.1–1.3 eV and 2.1–2.3 eV above lattice oxygen, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 45 publications
12
57
1
Order By: Relevance
“…Thetemperature can reportedly reach 2500 8 8Cfor CO 2 lasers,readily breaking CÀOand CÀN bonds and explaining the majority lack of zinc and calcium by vaporization in the EDX data after laser radiation. [16] After laser scribing,h igh-resolution X-ray photoelectron spectra in the O1sr egion (Supporting Information, Figure S1b) showed ad ecrease in the C À Od omain at 532.9 eV and an increase in the C=Od omain at 531.4 eV.Ahigher binding energy component (535.6 eV) could be observed in the spectrum of the LS-ePAD material but not in the unpatterned material;t his was because of the lattice oxygen of surface-adsorbed water vapor [21,22] present as environmental humidity during laser scribing.T he X-ray photoelectron spectra of N1s( Supporting Information, Figure S1a), indicated that the intensity of the N1sp eak significantly decreases after laser scribing, which agrees with the results of EDX analysis and the release of N 2 gas due to extreme local temperatures.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Thetemperature can reportedly reach 2500 8 8Cfor CO 2 lasers,readily breaking CÀOand CÀN bonds and explaining the majority lack of zinc and calcium by vaporization in the EDX data after laser radiation. [16] After laser scribing,h igh-resolution X-ray photoelectron spectra in the O1sr egion (Supporting Information, Figure S1b) showed ad ecrease in the C À Od omain at 532.9 eV and an increase in the C=Od omain at 531.4 eV.Ahigher binding energy component (535.6 eV) could be observed in the spectrum of the LS-ePAD material but not in the unpatterned material;t his was because of the lattice oxygen of surface-adsorbed water vapor [21,22] present as environmental humidity during laser scribing.T he X-ray photoelectron spectra of N1s( Supporting Information, Figure S1a), indicated that the intensity of the N1sp eak significantly decreases after laser scribing, which agrees with the results of EDX analysis and the release of N 2 gas due to extreme local temperatures.…”
supporting
confidence: 89%
“…Thep resence of these elements is attributed to presence of CaCO 3 and Kaolin, ahydrous aluminosilicate commonly used as the additive,c oating, and pigment in the paper industry. [16] After laser scribing,h igh-resolution X-ray photoelectron spectra in the O1sr egion (Supporting Information, Figure S1b) showed ad ecrease in the C À Od omain at 532.9 eV and an increase in the C=Od omain at 531.4 eV.Ahigher binding energy component (535.6 eV) could be observed in the spectrum of the LS-ePAD material but not in the unpatterned material;t his was because of the lattice oxygen of surface-adsorbed water vapor [21,22] present as environmental humidity during laser scribing.T he X-ray photoelectron spectra of N1s( Supporting Information, Figure S1a), indicated that the intensity of the N1sp eak significantly decreases after laser scribing, which agrees with the results of EDX analysis and the release of N 2 gas due to extreme local temperatures. [20] Additionally,t he intensity of the CÀOa nd nitrogen peaks decreased (Supporting Information, Figure S1a), indicating that these species may have recombined and released as gases due to the high local temperature generated by laser radiation.…”
mentioning
confidence: 99%
“…in binding energy implies a higher electron density. As presented in Figure 6, the Ti 2p biding energy for SiO 2 microfiber-covered with nano-TiO 2 decreased to 458.0 eV compared with the literature data 46 . The binding energy indicates a change in the chemical environment and an increase of electron densities at the Ti level.…”
Section: Xps Studies the Electron Density Of A Chemical Species Inflsupporting
confidence: 47%
“…. The formed Ti-O-Si bond involves the electrons transfer from Ti and Si towards oxygen, and taking into account that Si supplies fewer electrons than Ti, the electron densities level will decrease due to its electrons transfer towards oxygen 46 . The different behavior of our SiO 2 -TiO 2 system is due to the distinct synthesis method applied.…”
mentioning
confidence: 99%
“…Deconvolution of the peaks related to the dopants (Nb 3d and Ti 2p) yielded a single doublet for either material. Binding energies for the Nb 3d 5/2 and Ti 2p 3/2 components were 207.6 and 459.2 eV and were assigned to the fully oxidated states (Nb V and Ti IV ) [36,37]. Of note is that the amount of W V species differs from material to material.…”
Section: Resultsmentioning
confidence: 99%